2021
DOI: 10.3390/ijerph18084083
|View full text |Cite
|
Sign up to set email alerts
|

Fall 2020 COVID-19 Needs Assessment among New Jersey Secondary School Educational Professionals

Abstract: Secondary or high school (HS) educational professionals expressed concerns about dealing with environmental and occupational health and safety protocols due to COVID-19. Concerns related to fall 2020 school re-opening and getting back into in-person teaching—whether full-time, part-time or some other approved hybrid model—plus ongoing uncertainty with how the state and federal government will be handling matters about mandates for virtual learning, rapid testing, vaccine distribution, etc. These concerns were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…As mentioned in previous studies, age, gender, and race/ethnicity are demographic variables of interest and have been associated with an increase in vaccine hesitancy [ 3 ]. Survey questions were taken and adapted from the U.S. CDC Behavioral Risk Factor Surveillance Survey, the U.S. CDC Vaccine Confidence Survey Question Bank, and previous surveys conducted by NJSS [ 26 , 27 , 28 , 29 , 30 ]. Overall vaccine hesitancy is measured by vaccine status and booster status.…”
Section: Methodsmentioning
confidence: 99%
“…As mentioned in previous studies, age, gender, and race/ethnicity are demographic variables of interest and have been associated with an increase in vaccine hesitancy [ 3 ]. Survey questions were taken and adapted from the U.S. CDC Behavioral Risk Factor Surveillance Survey, the U.S. CDC Vaccine Confidence Survey Question Bank, and previous surveys conducted by NJSS [ 26 , 27 , 28 , 29 , 30 ]. Overall vaccine hesitancy is measured by vaccine status and booster status.…”
Section: Methodsmentioning
confidence: 99%
“…One NJSS training assignment asked about WBL program development and student worksite placements. Building on the NJSS statewide fall 2020 needs assessment, 10 this study's data about WBL during pandemic‐affected school years inform guidance to schools and employers to better address identified needs as COVID‐19 continues affecting communities. 11 …”
Section: Methodsmentioning
confidence: 99%
“…This, notably, is the responsibility of administrators and, as such raises the issue of administrative support as an important variable for consideration in the context of online teaching. In order to tackle thwarting of teachers' competence, responses from American high school teachers have highlighted necessary administrative support in several areas, such as providing tools and related professional development, counseling, support, tips, and resources, including those which can improve the interactions among teachers, students and parents ( 32 ). In terms of autonomy, several studies have reported the impact of lack of administrative support on reduced work autonomy among teachers ( 33 ) while advocating for specific administrative actions to enhance autonomy, including clear curriculum guidelines for online teaching, provision of appropriate online platforms, scheduling of “self-care” time during the day, surveying of teachers to assess their needs, and expressing interest in teachers' input.…”
Section: Introductionmentioning
confidence: 99%